Muon reconstruction performance of the ATLAS detector in proton-proton collision data at [Formula: see text]=13 TeV - Atlas Collaboration; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; Abolins, M; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; et al. (The European physical journal. C, Particles and fields, 2016)
This article documents the performance of the ATLAS muon identification and reconstruction using the LHC dataset recorded at [Formula: see text] TeV in 2015. Using a large sample of [Formula: see text] and [Formula: see text] decays from 3.2 fb[Formula: see text] of pp collision data, measurements of the reconstruction efficiency, as well as of the momentum scale and resolution, are presented and compared to Monte Carlo simulations. The reconstruction efficiency is measured to be close to [Formula: see text] over most of the covered phase space ([Formula: see text] and [Formula: see text] GeV). The isolation efficiency varies between 93 and [Formula: see text] depending on the selection applied and on the momentum of the muon. Both efficiencies are well reproduced in simulation. In the central region of the detector, the momentum resolution is measured to be [Formula: see text] ([Formula: see text]) for muons from [Formula: see text] ([Formula: see text]) decays, and the momentum scale is known with an uncertainty of [Formula: see text]. In the region [Formula: see text], the [Formula: see text] resolution for muons from [Formula: see text] decays is [Formula: see text] while the precision of the momentum scale for low-[Formula: see text] muons from [Formula: see text] decays is about [Formula: see text].